RARα supports the development of Langerhans cells and langerin-expressing conventional dendritic cells - Seika Hashimoto-Hill (Nature Portfolio, 2018)
Langerhans cells (LC) and langerin-expressing conventional dendritic cells are made from distinct progenitors and enriched in the distinct microenvironments of the skin. Here the authors show that these immune cells are regulated by retinoic acid receptor alpha (RARα) via simultaneous induction of LC-promoting Runx3 and repression of LC-inhibiting C/EBPβ.